Partisipasi Komunitas Sosial Terhadap Permasalahan Sosial Dan Berbagi Iftar Sebagai Implementasi Pemberdayaan Masyarakat Tasikmalaya - Hilmy Hazimatul Maishan; Jihad Fathulloh; Maulidya Magfira Rahmatillah; Rio Fernando; Nastiti Novitasari (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
There are two sides of humanity inherent in humans, namely humans as individual beings and humans as social beings. It is generally interpreted that humans as social beings cannot live without the help of others. However, usually we just want to know about the good conditions in an area, without us realizing that there is still a slum area. Even in big cities, the problems faced by the community are increasingly numerous and varied, ranging from personal problems to social problems, one of which is a slum area that cannot be solved without the help of other parties. In this case, the social community is present as a forum for the community to express their aspirations with others to determine common goals, none other than in solving problems that are being faced by the community. Not only its presence, but also the participation of the community in solving a problem that is being experienced by the community. In helping to solve problems, the community cannot move on its own without the support of related parties. For this reason, the Discussion Forum is fun to be held as a place to convey community ideas and ideas as well as an area for the existence of the community so that its existence is recognized and supported by every program that is carried out to help solve problems. Social problems. One of the tangible forms of the community in helping to overcome social problems, one of which is by sharing, be it food packages or others. In the diskusi asyik forum initiated by the Pager Asik community (Tasikmalaya City Movement) together with other communities who attended the Diskusi Asyik event as a follow-up to the event was to share 1800 iftar packages for communities in need spread to 17 points on the coast of Tasikmalaya city